The greening of European radical left parties: red and green politics. Issue 4 (1st October 2020) - Wang, Congcong; Keith, Dan
ABSTRACT: This article explores how European radical left parties (RLPs) respond to environmental issues and the extent to which green politics has been included in their programs and strategies. It shows that RLPs often have a greener policy profile than social democratic parties or right-wing parties. But compared with green parties, the members of the radical left party family are shown to be more moderate on environmental issues. The 'Red-Green' agenda adopted by RLPs is found to be characterized by social justice concerns. The article provides a comparative analysis which highlights considerable variation in the environmental policies of RLPs. The analysis shows that while most RLPs have modified their positions towards environmentalism, several variables, and in particular, the ideological heterogeneity found on the radical left can explain differences in their commitment to ecology. We also show that the willingness and capacity of RLPs to absorb such new issues have been shaped by party competition, environmental salience, and their organisational goals.